2007
DOI: 10.1111/j.1551-2916.2007.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Photoluminescence Properties of Mg‐Doped BaTiO3:Pr3+ Phosphor

Abstract: The photoluminescence of Mg‐doped BaTiO3:Pr3+ (Pr3+: 0.1 mol%) ceramics was investigated by changing the doping concentration of Mg and the sintering temperature. The results indicated that the intensity of red emission due to the 1D2→3H4 transition of Pr3+ exhibited significant dependence on both the Mg doping content and the sintering temperature; the strongest red emission intensity was observed for 2.0 mol% Mg‐doped ceramics sintered at 1050°C. An interpretation of the results obtained was made in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Graeve 6 ] (M = Mg, Ti) complex clusters. In general, this distortion is strongly associated with three common type of extrinsic factors: grain size (or crystallinity), 12,13 orientation, [14][15][16] and thermal stress (between film and substrate). 17 However, thermal stress is not the key factor of strong NIR emission in this study due to the substrate, film, and device structure are fixed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Graeve 6 ] (M = Mg, Ti) complex clusters. In general, this distortion is strongly associated with three common type of extrinsic factors: grain size (or crystallinity), 12,13 orientation, [14][15][16] and thermal stress (between film and substrate). 17 However, thermal stress is not the key factor of strong NIR emission in this study due to the substrate, film, and device structure are fixed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, modification of phosphor composition by chemical doping is a highly effective strategy for designing new materials and improving luminescent properties of already known compounds 15–18 . It was reported that Li + and Na + ions can enhance luminescence by generating oxygen vacancies, 19–22 or by promoting crystallinity, 22–24 or by altering the local symmetry of activator ions 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…A very similar trend was previously observed. 10) This result tells us that Ga doping has an effect of inducing a structural change from tetragonal to pseudocubic.…”
Section: Resultsmentioning
confidence: 99%